The Jossey-Bass Reader on the Brain and Learning - Publishers, Jossey-Bass (John Wiley & Sons, 2007)
This comprehensive reader presents an accessible overview of recent?brain research and contains valuable insights into how students learn and how we should teach them.?It includes articles from the top thinkers in both the brain science and K-12 education fields, such as Joseph LeDoux, Howard Gardner, Sally Shaywitz, and John Bransford. This rich and varied volume offers myriad perspectives on the brain, mind, and education, and features twenty-six chapters in seven primary areas of interest: An overview of the brain The brain-based learning debate Memory, cognition, and intelligence Emotional and social foundations The arts When the brain works differently
Keywords: Education / Teaching Methods & Materials / General